2008
DOI: 10.1111/j.1365-4632.2008.03177.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical 5‐aminolevulinic acid photodynamic therapy for the treatment of unilesional mycosis fungoides: a report of two cases and review of the literature

Abstract: PDT is effective and can be used successfully for MF treatment, particularly for patch and plaque stage MF, including unilesional MF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Ammann and Hunziker25 and Recio et al26 found complete histological cure of the plaques in full clinical remission and an absence of atypical lymphocyte infiltrates after treatment. Both described pigmentary changes with melanophages, fibrosis of the dermis, epidermal atrophy, and residual lymphocytes in the infiltrate.…”
Section: Photodynamic Therapy (Pdt)mentioning
confidence: 96%
“…Ammann and Hunziker25 and Recio et al26 found complete histological cure of the plaques in full clinical remission and an absence of atypical lymphocyte infiltrates after treatment. Both described pigmentary changes with melanophages, fibrosis of the dermis, epidermal atrophy, and residual lymphocytes in the infiltrate.…”
Section: Photodynamic Therapy (Pdt)mentioning
confidence: 96%
“…17 The histological response to treatment has been evaluated in a number of studies, though the results have been variable. Ammann et al 18 and Díez-Recio et al 19 reported complete histological cure and an absence of infiltrates of atypical lymphocytes in the plaques showing complete clinical response to treatment. Both groups described pigmentary changes with the presence of melanophages, dermal fibrosis, epidermal atrophy, and residual lymphocytes in the infiltrate.…”
Section: Mechanism Of Action Of Pdtmentioning
confidence: 97%
“…13,19,20 Conclusions PDT is a good, well-tolerated option for the treatment of localized MF plaques and provides a good cosmetic result. It is particularly useful in plaques that do not respond to the usual treatments and those located in problematic sites, such as the face or skin folds, or in areas at risk of poor healing.…”
Section: Practical Aspects Of Managementmentioning
confidence: 99%
“…ALA-PDT constitutes one of the most successful prodrugs used in cancer (17)(18)(19)(20). Different topical formulations of ALA, methyl-5-aminolevulinate (MAL) or other ALA-derivatives have been extensively used for treatment of superficial lesions such as skin malignancies, actinic keratosis, acne vulgaris, psoriasis or skin infections caused by bacteria or fungi (17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Different topical formulations of ALA, methyl-5-aminolevulinate (MAL) or other ALA-derivatives have been extensively used for treatment of superficial lesions such as skin malignancies, actinic keratosis, acne vulgaris, psoriasis or skin infections caused by bacteria or fungi (17)(18)(19)(20). MAL is the active component of Metvix®, a topical cream formulation containing the hydrochloride salt of methyl-5-aminolevulinate, a lipophilic methyl ester of ALA, with photosensitizer (PS) prodrug activity (21,22).…”
mentioning
confidence: 99%